Patología dermatológica facial asociada al uso de la mascarilla durante la pandemia causada por el virus Sars-CoV-2 - Villanueva A., Francisco; Zemelman D., Viviana (Revista Hospital Clínico Universidad de Chile, 2023)
The use of facemask has become a key element to prevent the infection of Covid-19. Its prolonged use, both, by health personnel and the general population, has caused the appearance of multiple adverse effects at the facial level; highlighting the report of symptoms such as discomfort with the mask, facial itching, redness, erythema, among others. The appearance of dermatological diseases such as acne, allergic and irritative contact dermatitis, and exacerbation of pre-existing pathologies such as acne, rosacea and seborrheic dermatitis are also frequent. Knowledge of these complications is important for their prevention and proper management.